Human Dermal Fibroblast Spheroid Overexpressing Matrix Metalloproteinase-1 Serves as a 3D Platform for In Vitro Drug Screening - Rajangam, Thanavel; Choi, Jong Hoon; Rashid, Md Mamunur; Chung, Haeun; Oh, Seung Ja; Jung, Byung Hwa; Kim, Sang-Heon (한국바이오칩학회, 2025)
Advanced three-dimensional (3D) in vitro models hold significant potential for replacing animals in preclinical investigations and accelerating translational research in testing new drug therapies. Overexpression of proteolytic enzyme matrix metalloproteinase-1 (MMP-1) correlates with increased degradation or reduced synthesis of type I collagen associated with connective tissue-related diseases and progression of certain cancers. In this study, we established an in vitro MMP-1 drug screening model by engineering 3D cell spheroids (3DCSs) of human dermal fibroblasts (hDFs), which secrete MMP-1, on a maltose-binding protein-basic fibroblast growth factor-immobilized substrate. We found that the hypoxic microenvironment and reactive oxygen species (ROS) synthesis generated in the interior region of 3DCSs extended towards the exterior regions during the culture period and were correlated with increased MMP-1 mRNA and protein expressions. Overexpression of MMP-1 led to the degradation of type I collagen in 3DCSs with increased culture time. 3DCSs treated with MMP inhibitors batimastat and marimastat showed decreased MMP-1 expression and increased drug uptake by hDFs in 3DCSs was verified using ELISA and liquid chromatography-mass spectroscopy, respectively. These results imply the significance of validating our 3D model as a potential tool for testing and developing anti-MMP-1 drug therapies and elucidating the underlying mechanisms of photoaging, arthritis, and certain cancers.